ChemInform Abstract: Selective Reduction of Amino Allenephosphonates: Preparation of α‐Amino Vinylphosphonates. Issue 23 (10th June 2014) - Adler, Pauline; Gomes, Filipe; Fadel, Antoine; Rabasso, Nicolas
Abstract A new protocol for the synthesis of a variety of the title compounds is presented with good to excellent stereoselectivity towards the (Z)‐conformation.